2006
DOI: 10.1093/hmg/ddl011
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate formation and phosphorylation of neurofilament-L Pro22 Charcot–Marie–Tooth disease mutants

Abstract: Charcot-Marie-Tooth disease (CMT) is the most common inherited peripheral nerve disorder. The causative gene for axonal type CMT2E has been identified as neurofilament light (NF-L) chain. Using cultured cells and in vitro assays, we analyzed the filament formation ability of Pro22 CMT mutant proteins of NF-L, P22S and P22T. NF-L Pro22 mutant proteins formed large aggregates in SW13- cells and cortical neurons and assembled into short twisty threads thinner than 10 nm filaments in vitro. Those threads associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 29 publications
1
65
0
1
Order By: Relevance
“…13 Functional studies have shown that missense mutant NEFL proteins disrupt the assembly with wild-type NEFL and with the NEFM and NEFH, and cause aggregation, resulting in the disruption of axonal neurofilament translocation and anterograde or retrograde axonal transport including mitochondria. [14][15][16] In this study, we found a homozygous nonsense mutation, Glu140-Stop, in one patient (case 2) in addition to four heterozygous missense mutations in five other patients. The parents of case 2 were first cousins, but they never complained of muscle weakness.…”
Section: Discussionmentioning
confidence: 50%
“…13 Functional studies have shown that missense mutant NEFL proteins disrupt the assembly with wild-type NEFL and with the NEFM and NEFH, and cause aggregation, resulting in the disruption of axonal neurofilament translocation and anterograde or retrograde axonal transport including mitochondria. [14][15][16] In this study, we found a homozygous nonsense mutation, Glu140-Stop, in one patient (case 2) in addition to four heterozygous missense mutations in five other patients. The parents of case 2 were first cousins, but they never complained of muscle weakness.…”
Section: Discussionmentioning
confidence: 50%
“…In previous studies, Pro22Ser and Pro22Thr mutants showed defects in filamentous network formation irregular aggregation in the SW13-cell, and the mutations abolish the Thr-Pro PDPK phosphorylation site in the NEFL head domain, which regulates filament assembly via phosphorylation (Pérez-Ollé et al 2005;Sasaki et al 2006). In our study, patients with the Pro22Arg mutation had the same demyelinating neuropathies as did patients with the Pro22Thr mutation; therefore, it seems that the Pro22Arg mutation also may abolish the Thr-Pro phosphorylation site of the head domain by PDPKs.…”
Section: Discussionmentioning
confidence: 92%
“…It has been suggested that Pro22 mutations abolish the Thr-Pro phosphorylation sequence of the head domain of NEFL by proline-directed protein kinases (PDPKs) (Sasaki et al 2006). In this study, we identified another NEFL Pro22Arg mutation, which was not reported in the inherited peripheral neuropathies mutation database (http://www.molgen.ua.ac.be/CMTMutations), and sought to determine its clinical and pathological characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is supposed that NEFL mutants not only infl uence the normal assembly of neurofi laments, but also cause aggregate formation that prevents transport or other physiological functions of the axon [53] . Moreover, NEFL mutants impede neurofilament assembly and transport in vivo and affect mitochondrial morphology by interfering with mitochondrial dynamics in a cellular model of the CMT2E/1F phenotype [54,55] .…”
Section: Nefl and The Associated Phenotypementioning
confidence: 99%